Effect of Increasing Levels of Web-Based Behavioral Support on Changes in Physical Activity, Diet, and Symptoms in Men With Prostate Cancer: Protocol for a Randomized Controlled Trial - Winters-Stone, Kerri M (JMIR Res Protoc, 2018)
BACKGROUND: More than 3.1 million men in the United States are prostate cancer survivors. These men may improve their physical function, quality of life, and potentially their prognosis by adopting healthier lifestyle habits. The internet provides a scalable mechanism to deliver advice and support about improving physical activity and dietary habits, but the feasibility and acceptability of a Web-based lifestyle intervention and the dose of support necessary to improve health behaviors are not yet known. OBJECTIVES: The Community of Wellness is a Web-based intervention focused on supporting exercise and healthy dietary practices for men with prostate cancer. The objectives of this study were to determine the feasibility, acceptability, and preliminary efficacy of the Community of Wellness Web portal among prostate cancer survivors by conducting a randomized controlled trial (RCT) comparing 4 levels of additive Web-based content and interaction with participants: Level 1 (Teaching; Control), Level 2 (Teaching + Tailoring), Level 3 (Teaching + Tailoring + Technology), and Level 4 (Teaching + Tailoring + Technology + Touch). METHODS: This is a single-blinded RCT comparing 3 levels of behavioral support within the Community of Wellness Web portal intervention (Levels 2 to 4) with each other and with the control condition (Level 1). The control condition receives general static Web-based educational information only on physical activity and dietary habits, self-efficacy for behavior change, motivation for physical activity, and changes in anxiety and treatment-related side effects. We will enroll and randomize 200 men with prostate cancer equally to 4 levels of the Community of Wellness Web-based intervention for 3 months (50 men per level). Surveys will be completed by self-report at baseline, 3 months (immediately postintervention), and 6 months (3 months postintervention). Feasibility and acceptability will be assessed by enrollment statistics, Web-based usage metrics, and surveys at the 3-month time point. We will also conduct focus groups after the postintervention follow-up assessment in a sample of enrolled participants to evaluate elements of usability and acceptability that cannot be obtained via surveys. RESULTS: Enrollment is ongoing, with 124 enrolled. Study completion (6-month follow-up) is expected by July 2019. CONCLUSIONS: The goal of the study is to identify the level of support that is feasible, acceptable, promotes behavior change, and improves health in men with prostate cancer to inform future efforts to scale the program for broader reach. TRIAL REGISTRATION: ClinicalTrials.gov NCT03406013; https://clinicaltrials.gov/ct2/show/NCT03406013 (Archived by WebCite at http://www.webcitation.org/73YpDIoTX). INTERNATIONAL REGISTERED REPORT IDENTIFIER (IRRID): PRR1-10.2196/11257